A Study on Components of Metabolic Syndrome among the Non-Diabetic Obese (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Metabolic syndrome is a cluster of interrelated metabolic abnormalities, including central obesity, insulin resistance, hypertension, dyslipidemia, and elevated fasting blood glucose levels. It significantly raises the risk of cardiovascular diseases and other health complications. This study focuses on the components of metabolic syndrome among non-diabetic obese individuals, who are particularly vulnerable to these metabolic disturbances due to excess adiposity. To assess the prevalence and associations of metabolic syndrome components among non-diabetic obese individuals. Materials and methods: A cross-sectional study was conducted at Chittagong Medical College Hospital from July 2020 to June 2021. The study enrolled 100 nondiabetic obese individuals aged 30 to 70 years, excluding those with diabetes, infections, liver or renal diseases, cardiovascular conditions, malignancies, endocrine disorders, or those on certain medications. Data on socio-demographic characteristics, anthropometric measures, serum lipid profiles, and fasting blood glucose levels were collected and analyzed using Microsoft Excel and IBM-SPSS v.20. Statistical significance was determined using the Student's ‘t’ test and chi-square (c2) test with a p-value < 0.05. Results: The majority of participants were under 40 years of age, predominantly female and mostly service holders. Elevated blood pressure was observed in 25% of participants. Anthropometric measures showed a mean BMI of 32.57 kg/m² and a mean waist circumference of 104.63 cm. Metabolic syndrome was present in 52% of participants. Dyslipidemia was prevalent, with 50% exhibiting elevated triglycerides and 46% having decreased HDL cholesterol. Notably, 42% of participants were prediabetic. Significant associations were found between metabolic syndrome and elevated triglycerides (p < 0.001), increased LDL cholesterol (p < 0.05), and decreased HDL cholesterol (p < 0.05). Conclusion: The study underscores the high prevalence of metabolic syndrome and associated dyslipidemia among non-diabetic obese individuals. The significant correlation between these metabolic abnormalities highlights the need for early detection and management strategies to mitigate the progression to type 2 diabetes and cardiovascular diseases.Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 8-11